Accelerating Thermal Stabilization by Pyrolytic Lignin for Partially Bio‐Based Carbon Fiber Precursor - Hui Shi; Qin Ouyang; Jingyu Wang; Jianwei Hao; Xianbo Huang (Macromolecular Materials and Engineering)
Abstract In this study, a partially bio‐based carbon fiber (CF) precursor is prepared by blending 32 wt% of pyrolytic lignin (PyL) with 68 wt% of poly(acrylonitrile‐co‐itaconic acid) (PANIA), and the effect of PyL on forming conjugated ladder structure during stepwise thermal stabilization is studied. The results of X‐ray photoelectron spectroscopy (XPS) reveal that PyL accelerates the formation of conjugated ladder structure at 230 °C during thermal stabilization for PANIA/PyL, which is 15 °C lower and 13 min earlier than PANIA. The acceleration on forming thermally stable conjugated ladder structure can be confirmed through Fourier‐transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). Moreover, the fiber stabilized at 230 °C is subsequently made into PANIA/PyL‐230 CF, which has relatively higher‐ordered graphitic structure and dense morphology without voids. The mechanism of PyL accelerating the formation of conjugated ladder structure during thermal stabilization is discussed.